Quantitative Secretomic Analysis of Trichoderma reesei Strains Reveals Enzymatic Composition for Lignocellulosic Biomass Degradation - Adav, Sunil S. (The American Society for Biochemistry and Molecular Biology, 2012)
Trichoderma reesei is a mesophilic, filamentous fungus, and it is a major industrial source of cellulases, but its lignocellulolytic protein expressions on lignocellulosic biomass are poorly explored at present. The extracellular proteins secreted by T. reesei QM6a wild-type and hypercellulolytic mutant Rut C30 grown on natural lignocellulosic biomasses were explored using a quantitative proteomic approach with 8-plex high throughput isobaric tags for relative and absolute quantification (iTRAQ) and analyzed by liquid chromatography tandem mass spectrometry. We quantified 230 extracellular proteins, including cellulases, hemicellulases, lignin-degrading enzymes, proteases, protein-translocating transporter, and hypothetical proteins. Quantitative iTRAQ results suggested that the expressions and regulations of these lignocellulolytic proteins in the secretome of T. reesei wild-type and mutant Rut C30 were dependent on both nature and complexity of different lignocellulosic carbon sources. Therefore, we discuss here the essential lignocellulolytic proteins for designing an enzyme mixture for optimal lignocellulosic biomass hydrolysis.